Social Security in China: On the Possibility of Equitable Distribution in the Middle Kingdom - Wang, Yanzhong (Springer Singapore : Imprint: Springer, 2017)
This book reviews the development of China's social security system from 1949 onwards and analyzes its features in each stage. By emphasizing the role of the social security system in regulating income distribution, it points out some problems in the current social security framework that are becoming apparent as the income gap continues to grow. It proposes various measures such as intensifying the reform of the social insurance fund, expanding old age insurance coverage, promoting health equality, and establishing a new rural medical security system that could be employed to improve the system's equitability, sustainability, and inclusivity.
Keywords: Social sciences.; Welfare economics.; Social policy.; elektronické knihy; electronic books